SYMBOLIC FORM IN PATRICK LOW’S PHOTOGRAPHY FROM 2004 - 2006 - Munusamy, Ravindran; Dolah, Jasni (2016)
The objective of this research is to highlight the importance of symbolism in photography. It is derived from the Preliminary Investigation (PI) whereby the result shows that the amateur photographers are lack of knowledge about symbolic form. Besides, there are also lacks of proper knowledge/method of getting good pictures. It will be done by analysing the best photograph from Patrick Low’s photography. He is the founder of EXES Studio and spent over 25 years in photography with achieving several international awards. Besides the MPA Ambassador of Malaysia, he was the first ever MPA Certified 3D Portraiture Master Photographer in the year of 2014. Besides his artworks, literature review in this research will support the fact about importance of symbolism in photography. The final outcome of this research is important because this will be a good platform to understand the theory and application of symbolic form in photography. Besides, this will be a good opportunity to know about Patrick Low and his artworks. For the amateur photographers, this research was important as they can learn a new method of taking good photographs by using symbolism theory.